FRI0284 Urinary excretion of CTX-II as a prognostic biomarker in spondyloarthritis. (23rd January 2014) - Trujillo, E.; Trujillo, M.D.M.; Ferraz, I.; Hernandez, V.; Delgado, E.; Flores, M.; Viotti, J.; de la Rosa, C.; Bustabad, S.
Abstract : Background: The search for biomarkers in spondyloarthritis is of great interest because of their diagnostic and prognostic role in the treatment of these diseases.In recent years cartilage has been shown to be a major target organ in spondyloarthritis. Cartilage degradation causes type II collagen fragments to be released into the bloodstream and these are then excreted in urine and can be used as biomarkers of cartilage destruction.In other diseases of the joints, elevated levels of urinary CTX-II (C-telopeptide fragments of type II collagen) have been associated with progression of radiological damage. Objectives: To compare the level of urinary CTX-II in patients with early-stage spondyloarthritis with urinary levels in healthy people of similar age and gender. To analyze the association between patient variables and diagnosis at 3 years of follow up. Patients: We included 68 patients aged <45 years, followed for at least 3 years by our department, and presenting at least one the following data suggestive of spondyloarthritis: inflammatory back pain, asymmetrical arthritis especially in lower limbs, enthesitis, dactylitis raquialgia or arthralgia, plus one of the following; psoriasis, IBD, anterior uveitis, family history of spondyloarthritis, radiographic sacroiliitis, HLA-B27 Methods: Urine samples were taken from all patients attending for the first time with suspected early spondyloarthritis. Urinary excretion of CTX-II was determined by immunoassay (ELISA) (ng/ml).We also determined CTX-II urinary excretion in a healthy control group (n=25) of similar age and sex. Because urinary levels were not normally distributed, all data were transformed into logarithms for analysis. Association analysis was performed with the following variables at 3 years: final diagnosis, HLA-B27, spondyloarthritis axial/peripheral ASAS, early involvement of large joints (hips, knees), presence of extra-articular manifestations (anterior uveitis, psoriasis) and anti-TNF therapy. Results: Urinary excretion of CTX-II in patients presenting for the first time with suspected early SA was significantly higher than in the healthy control group matched for age and sex (p<0.001). At 3 years follow up, the levels of urinary CTX-II in these patients were significantly higher in those who had predominantly peripheral involvement (spondyloarthritis peripheral ASAS) versus axial involvement, developed early large joint involvement and, due to high clinical activity and functional deficits (BASDAI and BASFI), required biological treatment. We found no association with HLA B27 or the presence of extra-articular manifestations. Conclusions: Urinary excretion of CTX-II in patients with early spondyloarthritis may be a prognostic biomarker since in our series it was associated with peripheral involvement and early large joint involvement, and the need for biological treatment in the first three years of follow-up. Disclosure of Interest: None Declared